Pelatihan Penyusunan Bahan Ajar berbasis Digital sebagai Pemberdayaan Guru Yayasan Sunan Ampel Poncokusumo - Rizki Amelia; Agus Mukti Wibowo; Fajar Rohman Hariri (IKIP PGRI Bojonegoro, 2023)
ABSTRACTThe Covid-19 pandemic has led to the emergence of various complex problems for educational institutions. The learning process which originally ran face-to-face directly in the classroom, had to be shifted to online or distance learning. Madrasah in the Poncokusumo District are included in schools that implement online learning during the Covid-19 pandemic. Teachers of the Sunan Ampel Foundation, Poncokusumo District, have difficulty implementing online learning, especially in making digital teaching materials. So far, teachers only use the WhatsApp platform in carrying out learning. The implementation of this service aims to provide empowerment to Sunan Ampel Foundation teachers in developing digital teaching materials. This service is carried out using the Participatory Action Research (PAR) method. This methods consists of planning, implementation and evaluation analysis as well as activity barriers. This activity was carried out for one month involving 55 teachers from the Sunan Ampel Pomcokusumo Foundation. In general, the training on the preparation of digital teaching materials went well. Training participants gain knowledge about the concept of teaching materials and how to compose digital teaching materials using the Canva application. In general, participants were also highly motivated to compose digital teaching materials. Some of them have succeeded in producing a digital teaching material product. Training participants gain knowledge about the concept of teaching materials and how to compose digital teaching materials using the Canva application. Keywords: online learning, madrasah teacher, digital teaching materials training ABSTRAKPandemi Covid-19 menyebabkan munculnya berbagai permasalahan yang kompleks bagi lembaga pendidikan. Proses pembelajaran yang semula berjalan secara tatap muka langsung di ruang kelas, terpaksa dialihkan menjadi tatap muka dalam jaringan atau yang disebut dengan Pembelajaran Jarak Jauh. Madrasah di wilayah Kecamatan Poncokusumo termasuk ke dalam sekolah yang menerapkan PJJ selama masa pandemi Covid-19. Guru Yayasan Sunan Ampel Kecamatan Poncokusumo mengalami kesulitan dalam melaksanakan pembelajaran online, khususnya dalam membuat bahan ajar digital. Selama ini, guru hanya menggunakan platform WhatsApp dalam melaksanakan pembelajaran. Pelaksanaan pengabdian ini bertujuan memberikan pemberdayaan pada guru yayasan sunan ampel dalam mengembangkan bahan ajar digital. Pengabdian ini dilaksanakan dengan metode Participatory Action Research (PAR), terdiri dari perencanaan kegiatan, pelaksanaan dan analisis evaluasi serta hambatan kegiatan. Kegiatan ini dilaksanakan selama satu bulan dengan melibatkan 55 guru yayasan sunan ampel pomcokusumo Secara umum, pelatihan penyusunan bahan ajar digital berjalan dengan baik. Peserta pelatihan mendapatkan ilmu mengenai konsep bahan ajar dan cara menyusun bahan ajar digital dengan menggunakan aplikasi canva. Kata Kunci: Pembelajaran online, Guru Madrasah, Pelatihan Bahan Ajar Digital